Political communication and capital toward swing voter cause in regional head elections 2020 in Karangasem Regency, Bali - Nuning Indah Pratiwi; Anak Agung Ngurah Anom Kumbara; Ni Wayan Widhiasthini (Penerbit Universiti Kebangsaan Malaysia, 2024)
A striking swing of voters marked the 2020 Regional Elections in Karangasem Bali. The incumbent pair, Mas Sumatri and Suari, who were predicted by a survey of 53.9% to win against Dana-Dipa by 37.2% during the campaign, actually showed a crushing defeat of 43.4% and a Dana-Dipa victory of 56.6%, according to the official results from the Karangasem General Election Commission (KPU). This study examines the phenomenon of swing voters in the 2020 Regional Elections in Karangasem by raising the problem of capital factors as the cause of swing voters in the 2020 Regional Elections in Karangasem and the political communication of candidates in minimising voter swing in the 2020 Regional Elections in Karangasem. This research uses a qualitative approach through observation techniques, interviews, document studies, and literature studies in its data collection. The data were analysed using capital theory in social practice. The results of this study show that the determinant factor, namely capital, occurs in the dynamics of swing voters and political communication in the 2020 Regional Elections in Karangasem by candidates delivering their vision and mission as their political communication messages. This research contributes as a reference related to the phenomenon of swing voters and the political communication strategies of candidates who contest to minimise swing voters.